SISTEM PENDEKTEKSI GAS CO RUANG PARKIR DI BASEMENT BERBASIS IOT - Iyus Rusmana; Sudiana (Retii, 2020)
Parking spaces located in malls or in tall buildings if the ground conditions are not wide enough, usually placed in basement spaces. There are many drawbacks that can be found from this condition, especially in terms of air exchange in the basement area. The air exchange must be designed in such a way that the air condition remains fresh. In this study, CO gas levels were detected by Gas sergeant MQ7. From this sensor with various stages initiating the Air Fan to enter fresh air, initiating the Exhaust Fan, initiating the communication system. The communication system, both buzzer and related party communication, is carried out after the MQ7 gas sensor approaches a predetermined threshold. Because if humans resemble high levels of CO gas, the risk is death. CO gas is a type of hazardous / poisonous gas. The effect of carbon monoxide gas for levels of 50 ppm is still relatively safe, while more than that it can cause harmful effects to the body. If in small amounts, inhaling CO can cause headaches, dizziness, lightheadedness, weakness and nausea. The air exchange system is designed in such a way that the energy consumed is more efficient. To be able to activate the sensor to remove CO gas and enter fresh air is easier automatically with the IOT system Keyword: CO gas, buzzer, MQ7 gas sensor, IOT System